SYSTEM DYNAMIC MODELING OF COMMUNICATION PROTOCOL FOR INCREASING SECURITY AND CONFIDENTIALITY OF INFORMATION SYSTEM IN SECOND FLEET COMMAND - Adi Widodo; Eko Krisdiono; Zainal Syahlan (Indonesian Naval Technology College STTAL, 2022)
The progress of information technology science is a current problem because, in addition to being able to contribute to improving welfare, progress, and the level of human civilization, it can also have a negative impact that causes unlawful actions and actions including criminal acts (crimes). Department of Information and Data Processing of Second Fleet Command has the main task of collecting, managing, and processing data as well as presenting information, research, and development in the Second Fleet Command and acting as an information technology service center. Telegraphic communication radio within the Indonesian navy is used for long-distance communication between ships, aircraft, and international coastal radio. Radio communication Telegraphy RTG uses international Morse signs, Q code, and Z code procedural signs to convey information or news. This research is planning a communication protocol scenario using the Mavlink and AX2.5 communication protocols. Each scenario will be run using simulation to get network performance. The results of the network performance measurement will be modeled using a dynamic system to get the best communication protocol as a proposal to improve the information security system at the Department of Information and Data Processing Second Fleet Command. Keywords: RTG, Mavlink, AX2.5, Radio communication Telegraphy, Communication protocol, network performance